Kibernetski kriminal: kazniva dejanja in kazenskopravna analiza - Šepec, Miha (University of Maribor Press, 2018)
Cybercrime: Criminal Offences and Criminal Law Analysis. The monograph represents a comprehensive criminal analysis of criminal offenses of cybercrime. These offenses are carried out with the help of a computer systems, aganins a computer system or as computer related content crime. The work before you uses criminal law dogmatic methods of studying and analyzing criminal offenses. The central part of the monograph is an analysis of all the known forms of cybercrime. We present contemporary trends in cybercrime and legal problems that appear in criminal law. The purpose of the monograph is to examine in detail the development, trends, specialties and dilemmas of manifestations of criminal offences of cyber crime, and provide solutions and guidelines for better consideration of these offences in theory and practice. At the same time, we will also provide solutions to how criminal law should face the ever more complex forms of cybercrime offences.